2020
DOI: 10.1186/s12891-020-03276-4
|View full text |Cite
|
Sign up to set email alerts
|

Infected Schmorl’s node: a case report

Abstract: Background: Schmorls node (SN) are mostly asymptomatic and incidental findings on MRI. However, sometimes they present like acute onset low back pain or acute exacerbation of chronic back pain after minor trauma. Case presentation: We present rare case of symptomatic infected SN in 67 years female patient presented with complains of low back pain radiating to right buttock. After initial conservative treatment failed subsequent imaging showed significant increase in size of lesion with focal signal changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…This finding might be useful to identify small SN. 2 Bone edema can also be seen on dual energy CT. 8,15 In this study, the SNs were clearly identified through CT scan to its size and multiple lesions. Sclerosis around the nodes' margin was also demonstrated in our CT scan findings.…”
Section: Discussionmentioning
confidence: 92%
“…This finding might be useful to identify small SN. 2 Bone edema can also be seen on dual energy CT. 8,15 In this study, the SNs were clearly identified through CT scan to its size and multiple lesions. Sclerosis around the nodes' margin was also demonstrated in our CT scan findings.…”
Section: Discussionmentioning
confidence: 92%
“…In one schema, aging degenerates the cartilaginous endplate through which the nucleus pulposus can penetrate if increased intradiscal pressure overcomes the weakened endplate as opposed to the annulus fibrosus [ 1 , 7 ]. Inherent mechanisms within the nucleus pulposus may trigger cytokines and an inflammatory response leading to pain or other symptoms [ 3 ]. Other theories for the generation of pain include the fracture of the endplate through which the nucleus pulposus herniates and activates nociceptors in the annulus fibrosus and periosteum of the vertebral bodies that are exacerbated by micromovements, swelling, and inflammation [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment is typically conservative, including anti-inflammatories, rest, physical therapy, bracing, or injections, including blocks. Symptoms typically resolve with conservative management, but they can last anywhere from two weeks up to six months [ 1 - 3 , 5 , 7 ]. However, the pain can be significant enough to impact ADL’s and impact quality of life as was described in this case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations